Membangun Jiwa Raga Peserta Didik Kristen Di Sekolah Menengah Kejuruan (SMK) Negeri 1 Parindu Kabupaten Sanggau Kalimantan Barat - Marthen Mau (Institut Nalanda, 2024)
Some students do not yet have a healthy body and soul. One of the most important healthy terms is spiritual health. Some Christian students are still classified as spiritually unhealthy; This is proven by the fact that there are still Christian students who miss studying during Christian religious education and character education lessons. The aim of this research is to explain how to build a healthy mind and body. Using qualitative research methodology through observation, documentation and research literature. The results of this research are that the more loyal they are in building the body and soul of Christian students, the more students will maintain and maintain physical and spiritual health. Conclusion: Christian students should have a healthy body and soul, therefore they need to be loyal and responsible in participating in the learning process of Christian religious education and character in addition to taking part in the project to strengthen the profile of Pancasila students (P5).